THE INFLUENCE OF WORK LIFE BALANCE AND JOB STRESS ON EMPLOYEE PRODUCTIVITY AT PT PLN (PERSERO) TOLITOLI: PENGARUH KESEIMBANGAN KERJA DAN STRES KERJA TERHADAP PRODUKTIVITAS KARYAWAN DI PT PLN (PERSERO) TOLITOLI - Aqfir Aqfir; Yuli Yuli; Edi Yanto (STIE MUJAHIDIN TOLITOLI, 2026)
This study aims to examine the effect of work-life balance and job stress on employee productivity at PT PLN (Persero) Tolitoli, both partially and simultaneously. This research employs a quantitative method with an associative approach. The population of this study consists of all employees of PT PLN (Persero) Tolitoli, totaling 40 employees. The sampling technique used is saturated sampling (total sampling), in which the entire population is taken as respondents. The primary instrument for data collection is a questionnaire developed using a Likert scale. Data analysis techniques include multiple linear regression analysis using SPSS software, accompanied by validity testing, reliability testing, classical assumption tests, and hypothesis testing through t-tests and F-tests. The results show that work-life balance partially has a positive and significant effect on employee productivity at PT PLN (Persero) Tolitoli. Meanwhile, job stress partially has a negative and significant effect on employee productivity. Simultaneously, work-life balance and job stress have a significant effect on employee productivity. The coefficient of determination indicates that a portion of the variation in employee productivity can be explained by work-life balance and job stress, while the remaining variation is influenced by other variables outside the research model.